The Role of English Language for High-Achieving Mayan Students in the Yucatan Region, Mexico - Miguel Antonio Pat López; Pedro Antonio Sánchez Escobedo (Universidad de La Sabana, 2019)
El rol del idioma inglés en estudiantes de alto rendimiento en la zona maya de Yucatán, México O papel da língua inglesa em estudantes de alto desempenho na área maia de Yucatán, México The purpose of this research was to identify the role of the level of proficiency in the English language with high-performing third-year students in the Mayan area of Yucatán, near a tourist region called the Riviera Maya. The aim was also to explore the relationship between learning a second language and the subsequent overall improvement in the academic performance of students. These 114 high-achieving students were selected from 1177 students who had taken a standardized English test administered in seven middle schools in the region. Subsequently, individual interviews were conducted with the 21 students with the highest level of English and a focus group of ten students with low-level scores. The results showed an improvement in the English language, as well as its influence in reaching academic prowess in other subjects. This initial study indicated that the reinforcement of English language skills had broader benefits on other academic performance. To reference this article (APA) / Para citar este artículo (APA) / Para citar este artigo (APA) Pat, M. A., & Sánchez, P. A. (2019). The role of English language for high-achieving Mayan students in the Yucatan region, Mexico. LACLIL, 12(1), 46-71. DOI: https://doi.org/10.5294/laclil.2019.12.1.3 Received: 13/04/2019 Approved: 22/08/2019